Genetic susceptibility in pharmacodynamic and pharmacokinetic pathways underlying drug-induced arrhythmia and sudden unexplained deaths. (September 2019) - Martinez-Matilla, M.; Blanco-Verea, A.; Santori, M.; Ansede-Bermejo, J.; Ramos-Luis, E.; Gil, R.; Bermejo, AM.; Lotufo-Neto, F.; Hirata, MH.; Brisighelli, F.; Paramo, M.; Carracedo, A.; et al.
Abstract: Drug-induced arrhythmia is an adverse drug reaction that can be potentially fatal since it is mostly related to drug-induced QT prolongation, a known risk factor for Torsade de Pointes and sudden cardiac death (SCD). Several risk factors have been described in association to these drug-induced events, such as preexistent cardiac disease and genetic variation. Our objective was to study the genetic susceptibility in pharmacodynamic and pharmacokinetic pathways underlying suspected drug-induced arrhythmias and sudden unexplained deaths in 32 patients. The genetic component in the pharmacodynamic pathway was studied by analysing 96 genes associated with higher risk of SCD through massive parallel sequencing. Pharmacokinetic-mediated genetic susceptibility was investigated by studying the genes encoding cytochrome P450 enzymes using medium-throughput genotyping. Pharmacodynamic analysis showed three probably pathogenic variants and 45 variants of uncertain significance in 28 patients, several of them previously described in relation to mild or late onset cardiomyopathies. These results suggest that genetic variants in cardiomyopathy genes, in addition to those related with channelopathies, could be relevant to drug-induced cardiotoxicity and contribute to the arrhythmogenic phenotype. Pharmacokinetic analysis showed three patients that could have an altered metabolism of the drugs they received involving CYP2C19 and/or CYP2D6, probably contributing to the arrhythmogenic phenotype. The study of genetic variants in both pharmacodynamic and pharmacokinetic pathways may be a useful strategy to understand the multifactorial mechanism of drug-induced events in both clinical practice and forensic field. However, it is necessary to comprehensively study and evaluate the contribution of the genetic susceptibility to drug-induced cardiotoxicity.